2018
DOI: 10.1038/s41598-018-20505-y
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-Mimetic Nanovesicles from Hepatocytes promote hepatocyte proliferation in vitro and liver regeneration in vivo

Abstract: The liver has great regenerative capacity after functional mass loss caused by injury or disease. Many studies have shown that primary hepatocyte-derived exosomes, which can deliver biological information between cells, promote the regenerative process of the liver. However, the yield of exosomes is very limited. Recent studies have demonstrated that exosome-mimetic nanovesicles (NVs) can be prepared from cells with almost 100 times the production yield compared with exosomes. Thus, this study investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 44 publications
1
49
0
Order By: Relevance
“…Cell‐derived mimetic nanovesicles (M‐NVs) are an emerging and potentially promising alternative to exosomes for clinical applicability, demonstrating reproducibility in protocol, cost‐effectiveness, and higher yield production rates. The benefits of M‐NVs address issues of relatively low quantities of exosomes produced by cells and the involvement of extensive isolation and purification procedures . Importantly, the biological activity and uptake of M‐NVs was confirmed in vitro using cellular uptake studies and in vivo biodistribution studies.…”
Section: Introductionmentioning
confidence: 99%
“…Cell‐derived mimetic nanovesicles (M‐NVs) are an emerging and potentially promising alternative to exosomes for clinical applicability, demonstrating reproducibility in protocol, cost‐effectiveness, and higher yield production rates. The benefits of M‐NVs address issues of relatively low quantities of exosomes produced by cells and the involvement of extensive isolation and purification procedures . Importantly, the biological activity and uptake of M‐NVs was confirmed in vitro using cellular uptake studies and in vivo biodistribution studies.…”
Section: Introductionmentioning
confidence: 99%
“…Miura et al (11) reported that in the rats undergoing 70 % PHx, ALT levels reached the highest level during fi rst 12 hours, and then decreased with time, reaching the levels similar to that of control rats at 48 hours. Comparable studies from the literature reported higher serum ALT levels in the PHx-treated groups compared to the Sham group (12) with a decline after treatment (3,13,14). Previous studies showed the rate of liver regeneration to usually and time-dependently increase in groups where PHx was performed (15,16).…”
Section: Discussionmentioning
confidence: 91%
“…Jang et al discovered that chemotherapeutic drug-loaded nanovesicles, as exosome mimetics, inhibited tumor growth in vitro and in vivo, with no adverse effects [47]; Wu et al first reported the preparation for exosome-mimetic nanovesicles (NVs) from primary hepatocytes with almost 100 times the production yield compared with exosomes. Meanwhile, NVs were demonstrated to have both components and biofunctions similar to exosomes from primary hepatocytes [48]. These findings indicate that exosome mimetics, serving as drug carriers to replace exosomes, can effectively overcome two common issues with exosomes: the difficulties of mass production and the time-consuming nature of the purification process.…”
Section: Exosomes As Proper Carriers To Deliver Target Drugsmentioning
confidence: 88%